2021
DOI: 10.3390/biom11081107
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals in Cancer Immune Checkpoint Inhibitor Therapy

Abstract: The interaction of immune checkpoint molecules in the tumor microenvironment reduces the anti-tumor immune response by suppressing the recognition of T cells to tumor cells. Immune checkpoint inhibitor (ICI) therapy is emerging as a promising therapeutic option for cancer treatment. However, modulating the immune system with ICIs still faces obstacles with severe immunogenic side effects and a lack of response against many cancer types. Plant-derived natural compounds offer regulation on various signaling casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 256 publications
(266 reference statements)
0
22
0
Order By: Relevance
“…A study on traditional Chinese medicine anti-tumor found that three typical natural products of Huangqin, oroxylin A, wogonin and baicalin, may overcome anti-cancer drug resistance by modulating the tumor immunosuppressive microenvironment ( 233 ). Natural products modulate immune checkpoint-related signaling molecules via multiple signaling cascades in the tumor microenvironment combined with immune checkpoint inhibitors (ICIs), which not only enhance the effectiveness of immunotherapy but also reduce the adverse effects of resistance ( 234 ). Signal transducer and activator of transcription 3 (STAT3) hyperactivation regulates immune responses in the tumor microenvironment by cytokines, growth factors, and G protein-coupled receptors to attenuate drug resistance and control cancer metastasis ( 235 ).…”
Section: Natural Products Regulate the Tumor Microenvironment To Over...mentioning
confidence: 99%
“…A study on traditional Chinese medicine anti-tumor found that three typical natural products of Huangqin, oroxylin A, wogonin and baicalin, may overcome anti-cancer drug resistance by modulating the tumor immunosuppressive microenvironment ( 233 ). Natural products modulate immune checkpoint-related signaling molecules via multiple signaling cascades in the tumor microenvironment combined with immune checkpoint inhibitors (ICIs), which not only enhance the effectiveness of immunotherapy but also reduce the adverse effects of resistance ( 234 ). Signal transducer and activator of transcription 3 (STAT3) hyperactivation regulates immune responses in the tumor microenvironment by cytokines, growth factors, and G protein-coupled receptors to attenuate drug resistance and control cancer metastasis ( 235 ).…”
Section: Natural Products Regulate the Tumor Microenvironment To Over...mentioning
confidence: 99%
“…Current research on this subject is focused on combining immune checkpoint inhibition with chemotherapy, PARP inhibitors, cancer vaccines, or NK cell therapy [ 128 ]. Furthermore, nutraceuticals are commonly used in the prevention and treatment of TNBC because plant-based food rich in phytochemicals can effectively modulate immune checkpoint-related signaling molecules such as PD-1 / PD-L1 [ 129 , 130 ]. Moreover, specifically designed nanoparticles with ligands on their surface can facilitate drug delivery by targeting to cancer cells to, for example, modulate immune responses.…”
Section: Current Immunotherapeutic Strategies Of Tnbcmentioning
confidence: 99%
“…At present, natural compounds have been shown to modulate intracellular biochemical reactions including the regulation of immune checkpoints such as PD-L1 and cytotoxic T-lymphocyte antigen 4 (CTLA-4), through a variety of signaling pathways. These effects have been confirmed in multiple cancer types including colon cancer ( 219 ). Previous studies have revealed that NF-κB, PI3K and MAPK signaling pathways were involved in the regulation of CRC via PD-L1 by resveratrol, piceatannol and panaxadiol ( 22 , 220 ).…”
Section: Discussionmentioning
confidence: 79%